2009
DOI: 10.1093/ndt/gfp310
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin (NGAL) reflects iron status in haemodialysis patients

Abstract: The findings demonstrated that HD patients have altered NGAL values probably because this protein is involved in the maintenance of iron equilibrium. Finally, NGAL might be proposed as a new tool in the assessment of iron deficiency and in the management of iron therapy for HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 15 publications
1
39
1
Order By: Relevance
“…Anemia and inflammation are known to induce NGAL. 33,34 In this study, we could not demonstrate any association between serum NGAL levels and CRP. Serum NGAL levels were higher in HD patients compared with healthy controls in our study confirming the previous studies 33 probably due to decreased clearance rather than increased inflammation in HD patients.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…Anemia and inflammation are known to induce NGAL. 33,34 In this study, we could not demonstrate any association between serum NGAL levels and CRP. Serum NGAL levels were higher in HD patients compared with healthy controls in our study confirming the previous studies 33 probably due to decreased clearance rather than increased inflammation in HD patients.…”
contrasting
confidence: 77%
“…NGAL levels were found to be significantly correlated with transferrin saturation, ferritin and inversely associated with serum hepcidin levels in previous studies. 32,33 Thus, decreased NGAL levels may be considered to represent decreased iron availability in HD patients. However, in our study, serum NGAL levels were not associated with hepcidin or other serum iron parameters.…”
mentioning
confidence: 99%
“…It follows that close monitoring of iron homeostasis is mandatory when sucroferric oxyhydroxide is administered to these subjects. On the other hand, CKD patients often show iron deficiency 63 and receive oral or intravenous iron supplementation. Several drug formulations are currently available, each of which is characterized by different iron content per pill (eg, ferrous gluconate: 300 mg, equivalent to 37.5 mg of elemental iron; ferrous sulfate: 329.7 mg, corresponding to 105 mg of elemental iron) and pharmacokinetic profile.…”
Section: Resultsmentioning
confidence: 99%
“…It may suggest a link between NGAL, iron metabolism, and inflammation. Bolignano et al [21] suggested that elevated NGAL was probably related to its involvement in iron equilibrium. They reported that NGAL was predicted by hsCRP, TSAT and spKt/V.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent issue of Nephrology Dialysis and Transplantation, Bolignano et al [21] suggested that altered NGAL values in haemodialysed patients were probably due to the fact that this protein was involved in iron metabolism. Since levels of hepcidin, a peptide known to be involved in iron metabolism [22], are also elevated in haemodialysed patients, in this study we tested the hypothesis whether NGAL might be correlated with hepcidin.…”
Section: Introductionmentioning
confidence: 99%